Enhanced Autophagy in GAB1-Deficient Vascular Endothelial Cells Is Responsible for Atherosclerosis Progression - Qian, Xin; Wang, Han; Wang, Yuli; Chen, Jiaquan; Guo, Xiangjiang; Deng, Haoyu (Frontiers in Physiology, 2021)
Autophagy is a host machinery that controls cellular health. Dysfunction of autophagy is responsible for the pathogenesis of many human diseases that include atherosclerosis obliterans (ASO). Physiologically, host autophagy removes aging organelles and delays the formation of atherosclerotic plaque. However, in ischemia event, dysregulated autophagy can be induced to trigger autosis, leading to an inevitable cellular death. Grb2-associated binder 1 (GAB1) is a docking/ scaffolding adaptor protein that regulates many cell processes including autophagy. Our study first reported that the protein expression of GAB1 significantly decreased in ASO. Mechanically, our results showed that inhibition of Akt(protein kinase B), the upstream of mTOR(mechanistic target of rapamycin), significantly enhanced autophagy by demonstrating the downregulation of p62/Sequestosome 1 expression and the upregulation of the ratio of LC3II/LC3I. Conversely, we found that the inhibition of ERK1/2 (extracellular signal-regulated kinases1/2), p38 and JNK (c-Jun N-terminal kinase) signaling pathway, respectively, significantly inhibited autophagy by demonstrating the upregulation of p62 expression and the downregulation of the ratio of LC3II/LC3I. Further, we demonstrated that knockdown of GAB1 significantly increased autophagy in HUVECs(human umbilical vein endothelial cells) via activation of MAPK(mitogen-activated protein kinase) pathways that include ERK1/2, p38 and JNK. Moreover, we found that knockdown of GAB1 profoundly inhibited HUVECs proliferation, migration and tube formation. Taken together, this study first suggests that GAB1 is a key regulator of autophagy in HUVECs. Targeting GAB1 may serve as a potential strategy for the atherosclerosis treatment.